Two-warehouse inventory model for non-instantaneous deteriorating items with partial backlogging and permissible delay in payments under inflation. (2017) - Palanivel, M.; Uthayakumar, R.
In this paper, two-warehouse economic order quantity (EOQ) model for non-instantaneous deteriorating items with permissible delay in payments under the effect of inflation and time value of money is presented in which the demand is considered as a deterministic function of selling price and advertisement cost. Also in this model, shortages are allowed and partially backlogged. The backlogging rate is dependent on the waiting time for the next replenishment. This model aids in minimising the total inventory cost by finding the optimal intervals and the optimal order quantity. Furthermore, numerical examples are provided to illustrate the proposed model, sensitivity analysis of the optimal solutions with respect to major parameters is carried out and some managerial inferences are obtained.